2021
DOI: 10.3390/w13121700
|View full text |Cite
|
Sign up to set email alerts
|

Deep Pools: Ecological Sanctuaries for Steindachneridion melanodermatum, a Large Endemic and Endangered Pimelodid of the Iguaçu River

Abstract: Steindachneridion melanodermatum, an endemic and endangered species, is the largest catfish in the Lower Iguaçu River basin. Currently, the wild population of this species no longer exists in most of this basin, probably due to the loss of habitat by successive hydroelectric dams. This study evaluated the spatial distribution and abundance of S. melanodermatum in the last free-flowing river stretch of approximately 190 km downstream from the Salto Caxias Dam, upstream of the Iguaçu Falls, as well as some tribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Calderon and An (2016) concluded that deep pools and shoals can alter the nutrient content of the water column, which in turn affects the distribution of chlorophyll, and that insectivores dominate in shoals, whereas omnivores and fish dominate in deep pools. De Assumpcao et al (2021) collected 180 specimens of high abundance in a protected area near Iguaçu Falls in the Iguaçu National Park. Twenty‐four deep pools were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Calderon and An (2016) concluded that deep pools and shoals can alter the nutrient content of the water column, which in turn affects the distribution of chlorophyll, and that insectivores dominate in shoals, whereas omnivores and fish dominate in deep pools. De Assumpcao et al (2021) collected 180 specimens of high abundance in a protected area near Iguaçu Falls in the Iguaçu National Park. Twenty‐four deep pools were identified.…”
Section: Introductionmentioning
confidence: 99%